An expanded palette of improved SPLICS reporters detects multiple organelle contacts in vitro and in vivo - Vallese, Francesca; Catoni, Cristina; Cieri, Domenico; Barazzuol, Lucia; Ramirez, Omar; Calore, Valentina; Bonora, Massimo; Giamogante, Flavia; Pinton, Paolo; Brini, Marisa; Cali, Tito (Nature Communications, 2020)
Membrane contact sites between virtually any known organelle have been documented and, in the last decades, their study received momentum due to their importance for fundamental activities of the cell and for the subtle comprehension of many human diseases. The lack of tools to finely image inter-organelle proximity hindered our understanding on how these subcellular communication hubs mediate and regulate cell homeostasis. We develop an improved and expanded palette of split-GFP-based contact site sensors (SPLICS) for the detection of single and multiple organelle contact sites within a scalable distance range. We demonstrate their flexibility under physiological conditions and in living organisms.